FORMATION OF A COGNITIVE COMPONENT IN SPIRITUAL AND PHYSICAL DEVELOPMENT OF A PERSONALITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article proposes a cognitive component of sports and physical culture, and also consider the problems of human formation as spiritual and bodily integrity.